Chemical structure dependent electrochemical degradation of antibiotics using Boron-doped Diamond Electrodes - Jumah, Rami; Alsalman, Safaa; Jum'h, Inshad; Al-Addous, Mohammad; Hrahsheh, Fawaz; Ghanem, Hanadi; Rosiwal, Stefan; Telfah, Ahmad (Journal of Environmental Chemical Engineering, 2024)
The electrochemical degradation of Amoxicillin (AMOX), Ciprofloxacin (CIP), and Streptomycin (STR) utilizing Boron-Doped Diamond Electrodes (BDD) was explored under varying levels of applied electrical current density and initial buffer acidity. These pharmaceuticals were carefully selected to showcase the efficiency of electrochemical oxidation across different major chemical structure antibiotic families. The results demonstrated a positive correlation between higher applied current density and the elimination of antibiotics, as well as enhanced chemical oxygen demand (COD) removal rate. However, a negative impact was observed on the specific energy consumption (SEC). Notably, the highest antibiotics and COD removal efficiencies, along with the lowest SEC, were achieved at an applied current density of 45 mA/cm2. Furthermore, the investigation highlighted the significant influence of the chemical structure of the selected antibiotics on their degradation process. At a current density of 15 mA/cm2 and after 24 minutes of treatment, the degradation order was found to be AMOX > CIP > STR, with respective antibiotic removal efficiencies of 98.5 %, 87.8 %, and 81.1 %. Similarly, after 90 minutes of treatment, the COD degradation efficiency followed the order AMOX (50.4 %) > CIP (47.3 %) > STR (44.6 %), accompanied by decreasing levels of specific energy consumption, measuring 59, 61, and 67 kWh/kg COD, respectively, with an average current efficiency of 23–26 %. The pH had a significant effect on the streptomycin degradation rate, while it had a negligible impact on the degradation rate of ciprofloxacin. These findings shed light on the critical role of the pharmaceuticals' chemical structures and environmental conditions in governing the efficiency of their electrochemical degradation.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Amoxicillin; Boron-doped diamond (BDD); Ciprofloxacin; Electrochemical oxidation; Streptomycin; Water pollutant